Enzymatic generation of whey protein hydrolysates under pH-controlled and non pH-controlled conditions: Impact on physicochemical and bioactive properties. (15th May 2016) - Le Maux, Solène; Nongonierma, Alice B.; Barre, Chloé; FitzGerald, Richard J.
Highlights: Whey protein hydrolysates were generated with two enzyme preparations. Hydrolysis was carried out under pH-controlled and non pH-controlled conditions. The peptide profiles obtained were dependent on the pH condition used. Hydrolysis pH conditions impacted on antioxidant and antidiabetic properties. The impact of pH condition on hydrolysis bioactivity was enzyme dependent. Abstract: Enzymatic hydrolysis of whey protein (WP) was carried out under pH-controlled and non pH-controlled conditions using papain and a microbial-derived alternative (papain-like activity). The impact of such conditions on physicochemical and bioactive properties was assessed. WP hydrolysates (WPH) generated with the same enzyme displayed similar degree of hydrolysis. However, their reverse-phase liquid chromatograph mass spectrometry peptide profiles differed. A significantly higher oxygen radical absorbance capacity (ORAC) value was obtained for WP hydrolysed with papain at constant pH of 7.0 compared to the associated WPH generated without pH regulation. In contrast, there was no significant effect of pH regulation on dipeptidyl peptidase IV (DPP-IV) properties. WP hydrolysed with papain-like activity under pH regulation at 7.0 displayed higher ORAC activity and DPP-IV inhibitory properties compared to the associated WPH generated without pH regulation. This study has demonstrated that pH conditions during WPH generation may impact on peptide release and therefore on WPH bioactive properties.